From Conservative Alternative to Vanishing Frontier: Canada in American Travel Narratives, 1799-1899 - DOYLE, JAMES (Canadian Review of American Studies, 1974)
To many nineteenth-century Americans, Canada was an enigma. "Neither a republic nor a monarchy, but merely a languid expectation of something undefined."1 declared Charles Dudley Warner on the basis of a visit to Cape Breton Island in 1874, and his remark is typical of the bemused disapproval which American observers often expressed after a brief look at one corner or another of the northern provinces. Warner was one of several noteworthy American authors who visited Canada in the nineteenth century. Writers as various as Henry Thoreau, William Dean Howells, Henry James, Walt Whitman, Hamlin Garland - as well as many less noteworthy figures - tried to express their experience of Canada in some way that would satisfactorily characterize the country, particularly by relating it to their own national experience. The resultant range of opinion is a virtual summary of nineteenth-century American political and social thought, from an extreme conservative enthusiasm for a well-ordered hierarchical society, through republican suspicion of a British colony with a large Roman Catholic population, or sympathy with a sparsely populated and westward-expanding frontier nation, to doubts and regrets about the ultimate direction of civilization in North America.